Konsep Arsitektur Futuristik pada Perencanaan Pusat Pustaka dan Taman Pintar di Kabupaten Banyumas - Fitriyani, Nur Laeli; Nursruwening, Yohana; Widyandini, Wita (Retii, 2024)
Indonesia faces social inequality where population growth and education levels do not progress in tandem. The population is growing rapidly, but education is not expanding at the same pace. Efforts to minimize this disparity have not been effective enough, thus alternative solutions through an architectural approach are needed to improve the quality of education. This involves planning for a Library Center and Smart Park in Banyumas Regency. The concept of Futuristic Architecture is applied to create a modern and innovative area by utilizing advanced technologies such as artificial intelligence, virtual reality, and renewable energy. The planning of the Library Center and Smart Park in Banyumas Regency is carried out using qualitative methods to gain in-depth information about the planning, and quantitative methods to estimate the number of users for the designed area. It is hoped that this approach can enhance the enthusiasm for learning and the quality of education in Banyumas Regency, and assist policymakers in devising more effective strategies to improve educational facilities.